К 40-летию кафедры автоматизации химико-технологических систем и экологического мониторинга - Тошинский, Владимир Ильич; Литвиненко, Игорь Иванович (НТУ "ХПИ", 2005)
Brief data on a history of development of faculty аre submitted. The basic directions of scientific activity are given, the significant role of the international cooperation in increase of efficiency research and study is shown.
Keywords: история кафедры; научная деятельность кафедры